Premature loss of primary anterior teeth due to trauma – potential short‐ and long‐term sequelae. Issue 2 (20th October 2013) - Holan, Gideon; Needleman, Howard L.
Abstract Traumatic dental injuries (TDIs) can result in the premature loss of primary anterior teeth due to an immediate avulsion, extraction later after the injury because of poor prognosis or late complications, or early exfoliation. There are a number of potential considerations or sequelae as a result of this premature loss that have been cited in the dental literature, which include esthetics, quality of life, eating, speech development, arch integrity (space loss), development and eruption of the permanent successors, and development of oral habits. This article provides a comprehensive review of the dental literature on the possible consequences of premature loss of maxillary primary incisors following TDI.